PEMBANGUNAN EKONOMI KELUARGA PERSPEKTIF ISLAM (STUDI ANALISIS KELUARGA NELAYAN KOTA LHOKSEUMAWE) - febi, febi; Budiman, Iskandar (IAIN Langsa, 2016)
AbstractThe main problem discussed here is The Domestic Responsibility of Economic Development in Islam, focusing on economic growth analisis of fisherman community in Lhokseumawe. The objective of this discussion is to illustrate the whole things related to right and obligation of husband and wife in the household, particularly the fisherman?s family. This is a qualitative-explorative study. The primary source of data in this study was found from participant observation, questionnaires, and from interview, while the secondary data was collected through document analysis as well as library research which were related to economic growth issues of fisherman?s community. The analysis of data was done through interpretation of proposition which was based on the opinion of Islamic Law Expert (Fuqaha) or Islamic scholars. The result of research shows that Islam recommends that the position of man and women or husband and wife have the same right and obligation based on Islamic Shari?ah. According to Quranic values and Islamic point of view, the position of husband and wife are the same in term of right and obligation in surviving family and educating children, in associating with the community, and also the same right before the law. In case of family economic development, especially for lower scale family as it is experienced by the fisherman?s family in Lhokseumawe, the involvement of wife in working to survive the family is significantly influenced for increasing family income. The efforts of women or wifes to earn for living are very limited because most of the fisherman?s community think that the main responsibility or obligation of earning money to survive the family is burdened exclusively on husband as the head of family. It is necessary to inform and enlighten comprehensively that Islamic Shari?ah has recommended the same right and obligation between husband and wife forimproving welfare of their family.Keywords: Domestic Responsibility, fisherman?s family, economic development